Pengaruh Konsentrasi Larutan Natrium Hipoklorit terhadap Stabilitas Dimensi Cetakan Alginat - Resty Pratama Nurliyani; Fildzah Nurul Fajrin; Aria Fransiska (Faculty of Dentistry Universitas Andalas, 2022)
Alginate is one of the transmission media of cross infection, therefore disinfection is necessary before proceeding to the next step. One of the ways to disinfection alginate is by spraying sodium hypochlorite. The concentration of sodium hypochlorite solution that can be used as a disinfection solution according to the ADA are 0.5%, 1%, 2%, 5%, and 5.25%. The disinfection on alginate should not change dimensions. ADA states that impression materials should not change more that 0,5% from its original size. The purpose of this study was to determine the effect of sodium hypochlorite concentration on changes in alginate dimensions. The method of this study was an experimental laboratory with post test only control group design with 24 samples. The alginate was sprayed with aquadest solution as a control, sodium hypochlorite solution with concentrations of 0.5%, 1%, 2%, 5%, 5.25% then filled with gypsum. The dimensional stability was measured using a digital caliper. Data were analyzed by One Way Anova and then followed by Post Hoc LSD Test. The result of this study showed that the largest change in dimensional stability occurred in 0.5% sodium hypochlorite solution, while the smallest was in the 5.25%. One Way Anova test showed that there was a significant difference (p<0.05) between spraying with 0.5%, 1%, 2%, 5%, 5.25% sodium hypochlorite solution. The conclusion of this study was there is an effect of the concentration of sodium hypochlorite solution on the dimensional stability of the alginate impression.